2003
DOI: 10.1007/s00204-002-0427-6
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-induced oxidative stress and effect of antioxidants in human lymphocytes

Abstract: The purpose of this study was to evaluate the oxidative effect in human lymphocytes after acute nickel (Ni) treatment for 1 h; levels of intracellular reactive oxygen species (ROS), lipid peroxidation (LPO) and hydroxyl radicals ((*)OH) were examined in isolated lymphocytes. The potential effects of antioxidants were also examined. After acute treatment, NiCl(2) (0-10 mM) significantly decreased the viability of lymphocytes. NiCl(2) appear to increase the degree of dichlorofluorescein (DCF) fluorescence and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 24 publications
6
43
0
1
Order By: Relevance
“…It has been reported that administration of nickel resulted in the accumulation of iron, which in turn generate ROS via Haber-Weiss and Fenton's reaction [35,46]. The significant decrease in reduced glutathione in nickel treated group was correspondingly with previous reports [47,48]. The results showed also that nickel administration induced a significant decrease SOD, CAT and GSH-Px activities.…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported that administration of nickel resulted in the accumulation of iron, which in turn generate ROS via Haber-Weiss and Fenton's reaction [35,46]. The significant decrease in reduced glutathione in nickel treated group was correspondingly with previous reports [47,48]. The results showed also that nickel administration induced a significant decrease SOD, CAT and GSH-Px activities.…”
Section: Discussionsupporting
confidence: 78%
“…NiCl 2 -induced human lymphocyte toxicity may be mediated by oxygen radical intermediates [15]. Our previous studies have also shown that dietary NiCl 2 causes intestinal and splenic oxidative damage [12] [16].…”
mentioning
confidence: 91%
“…Symptoms of Ni toxicity (e.g., reduced photosynthesis and respiration rate, lower germination of seeds and decrease in root biomass) are observed at 0.19-0.85 lmol kg -1 . Nickel toxicity is also accompanied by impaired nutrient uptake, metabolism, and gas exchanges in plants (Molas, 1997;Chen and Lin, 2003;Duman andOturk, 2009). Song-Tao et al (2010) showed that Ni at 100, 200, 400, and 800 lM levels resulted in significant decrease of plant root and shoot fresh weight.…”
Section: Introductionmentioning
confidence: 98%